Molecular Basis of the Polydispersity of Mucins: Implications for the Generation of Saccharide Diversity. Issue 3 (June 1999) - Bhavanandan, Veer. P.; Gupta, Dwijendra; Woitach, Joseph; Guo, Xiaoxuan; Jiang, Weiping
Abstract : Secreted epithelial mucins are large macromolecules which exhibit extreme polydispersity, the molecular basis of which is not fully understood. We have obtained partial sequences of two genes (BSM1 and BSM2) coding for two distinct molecules. This is the first time that such closely-related genes have been identified for any mucin from an animal. We propose that a combination of multiple homologous genes, alternative splicing, differential glycosylation, and additional post-translational processing all contribute to the extreme polydispersity of mucins. The multiple domain structure and non-identical tandem repeats are also very important for the generation of the saccharide diversities of mucins.